2013
DOI: 10.1021/jm400768f
|View full text |Cite
|
Sign up to set email alerts
|

Highly Potent HIV-1 Protease Inhibitors with Novel Tricyclic P2 Ligands: Design, Synthesis, and Protein–Ligand X-ray Studies

Abstract: The design, synthesis, and biological evaluation of a series of HIV-1 protease inhibitors incorporating stereochemically defined fused tricyclic P2-ligands are described. Various substituent effects were investigated in order to maximize the ligand-binding site interactions in the protease active site. Inhibitors 16a and 16f showed excellent enzyme inhibitory and antiviral activity while incorporation of sulfone functionality resulted in a decrease in potency. Both inhibitors 16a and 16f have maintained activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 42 publications
(97 reference statements)
1
39
0
Order By: Relevance
“…This ligand was converted to the desired inhibitor as described previously. 14,23 The sigmatropic rearrangement product 9 is an effective intermediate for the synthesis of substituted P2-ligands. As shown in Scheme 2, the hydroxyl group was converted to methyl ether 13 using NaH and methyl iodide in THF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This ligand was converted to the desired inhibitor as described previously. 14,23 The sigmatropic rearrangement product 9 is an effective intermediate for the synthesis of substituted P2-ligands. As shown in Scheme 2, the hydroxyl group was converted to methyl ether 13 using NaH and methyl iodide in THF.…”
Section: Resultsmentioning
confidence: 99%
“…cis: R f = 0.38 (10% ethyl acetate/hexanes). [α] 23 D = −12.5 ( c 1.01, CHCl 3 ). 1 H NMR (300 MHz, Chloroform-d) δ 6.17 (dd, J = 11.4 Hz, 7.1 Hz, 1H), 5.76 (d, J = 11.7 Hz, 1H), 5.52 (q, J = 7.1 Hz, 1H), 4.24 – 4.10 (q, J = 7.5 Hz, 2H), 4.10 – 3.97 (m, 1H), 3.90 – 3.76 (d, J = 16 Hz, 1H), 1.67 – 1.61 (m, 2H), 1.50 (s, 3H), 1.39 (s, 3H), 1.28 (t, J = 7.1 Hz, 3H).…”
Section: Methodsmentioning
confidence: 99%
“…We also recently reported that a few HIV protease inhibitors, GRL-0519 containing tris-THF (18,19) and GRL-04810 and GRL-05010, show good CNS penetration in a blood-brain barrier (BBB) reconstruct model in vitro (20). In the present work, we examined and characterized the nonpeptidic HIV-1 protease inhibitor GRL-0739 (21), which contains the cyclohexyl-bis-THF moiety and a sulfonamide isostere (Fig. 1).…”
mentioning
confidence: 94%
“…12,13 Interestingly, our recent work indicated that the top oxygen of tris-THF may not be critical to the overall potency of the inhibitor. 14 In an effort to ascertain the contribution of the middle oxygen of the tris -THF ligand toward the ligand binding site interactions, we sought to synthesize the corresponding syn - anti - syn - and syn-syn-syn- fused 1,6- dioxatriquinane derivatives and compare enzyme inhibitory activity of the analogs with inhibitor 3 . Herein, we report our enantioselective syntheses of (3 R ,3 aS ,3 bR ,6 aS ,7 aS )-octahydro-2 H -cyclopenta[1,2- b :4,3- b′ ]-bis-furan-3-ol and (3 R ,3 aS ,3 bS ,6 aR ,7 aS )-octahydro-2 H -cyclopenta[1,2- b :4,3- b′ ]-bis-furan-3-ol using cascade radical cyclization and enzyme-catalyzed desymmetrization as the key steps.…”
mentioning
confidence: 99%
“…Optically active ligand alcohols 12 and 17 were reacted with p -nitrophenyl chloroformate in the presence of N -methyl morpholine in CH 2 Cl 2 at 23°C for 12 h to provide carbonates 18 and 19 in 60% and 62% yield respectively. 14 Reaction of these activated carbonates with amine 20 in the presence of diisopropylethylamine (DIPEA) in CH 2 Cl 2 at 23°C for 12 h furnished inhibitors 4 and 21 in 65% yield. 25 These compounds showed satisfactory analytical data.…”
mentioning
confidence: 99%